2017
DOI: 10.4172/2473-6449.1000123
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Sleep Quality among Adolescent Athletes

Abstract: Objectives: This study used a cross-sectional experimental design to examine the association between sleep quality and sports performance among adolescent recreation team-sports athletes in Hong Kong. By investigating the factors that affect sleep quality, it intended to arouse awareness of coaches and athletes the importance of sleeping so that they can improve training and competition performance.Methods: Hundred and twelve male and female participants with age range from 12 to 17 were involved in this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…To feel rested, the literature has demonstrated that elite athletes need ~8.3 h of sleep [64,65]. Moreover, adolescent athletes achieve, on average, ~6.3 h [47,66,67] of sleep, demonstrating a discrepancy between sleep recommendations and actual sleep achieved [42,68,69]. Sleep-wake cycles also undergo development during adolescence whereby adaptation occurs in sleep regulation during this phase [68].…”
Section: Sleep Adaptations During Adolescencementioning
confidence: 99%
“…To feel rested, the literature has demonstrated that elite athletes need ~8.3 h of sleep [64,65]. Moreover, adolescent athletes achieve, on average, ~6.3 h [47,66,67] of sleep, demonstrating a discrepancy between sleep recommendations and actual sleep achieved [42,68,69]. Sleep-wake cycles also undergo development during adolescence whereby adaptation occurs in sleep regulation during this phase [68].…”
Section: Sleep Adaptations During Adolescencementioning
confidence: 99%
“…Indeed, studies have shown that student athletes have more variable sleep patterns [ 35 ], tend to sleep less [ 32 ] and report high levels of daytime sleepiness [ 36 ]. There are several possible reasons why athletic populations may experience increased daytime sleepiness and worse sleep quality; heightened or excessive physical activity, high supplement intake (e.g., caffeine), increased post-exercise body temperature and/or elevated levels of fatigue and pain, and increased sympathetic nervous system activation, could all feasibly negatively impact sleep quality [ 37 39 ]. Consequently, there is a growing interest in dietary strategies that could enhance sleep quality in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, while the AAP does not recommend the stimulant caffeine to be consumed by adolescents [7], 30-50% report ingesting it [8], which may alter their sleep [9]. Youth athletes face these challenges to their sleep with the additional factors of (a) practice, competition, and travel times that may disrupt sleep [10,11], (b) physical and mental stressors of athletic performance [12], and (c) pain and recuperation due to injury [13].…”
Section: Introductionmentioning
confidence: 99%
“…This review examines contemporary variables leading to sleep debt in adolescent female athletes (FA) including blue light from Fig. 1 Contemporary independent variable impacting sleep and the potential dependent physiological variables [7,11,15,[22][23][24][25][26][27][28]. Sleep is broadly indicated in this diagram to include the complex physiological mechanisms that occur as a result of sleep debt.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation